2018
DOI: 10.1021/acs.jpcc.8b02693
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardant and Stable Li1.5Al0.5Ge1.5(PO4)3-Supported Ionic Liquid Gel Polymer Electrolytes for High Safety Rechargeable Solid-State Lithium Metal Batteries

Abstract: Recently, poor security in conventional liquid electrolytes and high interfacial resistance at the electrode/electrolyte interface are the most challenging barriers for the expanded application of lithium batteries. In this regard, easy processing and flexible composite ionic liquid gel polymer electrolytes (ILGPEs) supported by Li1.5Al0.5­Ge1.5­(PO4)3 (LAGP) are fabricated and investigated. The electrolyte is effectively combined with good electrochemical performances and thermal safety. Among these, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 36 publications
2
40
0
2
Order By: Relevance
“…Fig. 4 summarizes the room temperature ion conductivity and Li + ion transference number of ionic liquid electrolytes [25,26,[65][66][67]69,[82][83][84][85][86][87][88][89][90][91][92][93][94][95]. It can be observed that the room temperature ionic conductivities of both liquid electrolytes and composite electrolytes are above 10 -4 S/cm due to the high ionic conductivity and plasticizing effect of ionic liquids.…”
Section: Polymerized Ionic Liquidsmentioning
confidence: 99%
“…Fig. 4 summarizes the room temperature ion conductivity and Li + ion transference number of ionic liquid electrolytes [25,26,[65][66][67]69,[82][83][84][85][86][87][88][89][90][91][92][93][94][95]. It can be observed that the room temperature ionic conductivities of both liquid electrolytes and composite electrolytes are above 10 -4 S/cm due to the high ionic conductivity and plasticizing effect of ionic liquids.…”
Section: Polymerized Ionic Liquidsmentioning
confidence: 99%
“…The electrolyte displayed high ionic conductivity and low crystallinity. Flexible composite ionic liquid gel polymer electrolytes (ILGPEs) supported by Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 (LAGP) were fabricated and investigated by Guo et al for improving the electrochemical performance and thermal safety of the batteries [48]. They optimized 10% LAGP for the electrolyte.…”
Section: Gel Polymer Electrolytesmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] Moreover, gel electrolyte interlayers were introduced in ceramic-based solid state batteries, which displayed a remarkable wettability toward the Li surface, with high ionic conductivity at room temperature thanks to the composition of the polymer and liquid. 26,27 However, a detailed analysis of the interfacial resistance of the multilayer LAGPbased composite electrolyte has been rarely reported, and the interaction between the ceramic layer and the polymer layer has yet to be understood.…”
Section: Introductionmentioning
confidence: 99%